Проведення експертизи якості знань в системі підготовки бакалаврів у ТДАТУ - Болтянська, Наталя Іванівна; Болтянская, Наталья Ивановна; Boltianska, Natalia; Болтянський, Олег Володимирович; Болтянский, Олег Владимирович; Boltianskyi, Oleh (ТДАТУ, 2018)
UK: В статті описано методику проведення експертизи якості знань в системі підготовки бакалаврів, зокрема, створення системи атестації контролю якості освіти, якій би довіряло європейське співтовариство і в масштабах України, і всередині університету. EN: The article describes the methodology for carrying out the examination of the quality of knowledge in the system of preparation of bachelors, in particular, the creation of a certification system for the quality control of education, which would be trusted by the European community both on the scale of Ukraine and within the university.
Conducting the examination of quality knowledge in the training system of bacalavers to TSATU
Keywords: підготовка бакалаврів; системи атестації; якості освіти; кредит; знання; уміння; навички; діагностика якості знань; тестовий контроль; preparation of bachelors; attestation system; education quality; credit; knowledge; skills; diagnostics of knowledge quality; test control